Choosing and Using Astronomical Filters - Griffiths, Martin (The Patrick Moore Practical Astronomy Series, 2015)
As a casual read through any of the major amateur astronomical magazines will demonstrate, there are filters available for all aspects of optical astronomy. This book provides a ready resource on the use of the following filters, among others, for observational astronomy or for imaging: Light pollution filters Planetary filters Solar filters Neutral density filters for Moon observation Deep-sky filters, for such objects as galaxies, nebulae, and more Deep-sky objects can be imaged in much greater detail than was possible many years ago. Amateur astronomers can take photographs that rival those of professional observatories! The ability to do this has been brought about by the revolution in CCD cameras and improved filters. The book pinpoints which astronomical objects are best observed with which filters. Post-processing (using Photoshop) is also discussed, since it is helpful in further improving filtered astro images. The last part of the book is an observational guide to 100 deep sky objects that benefit from the use of filters - all personally observed by the author - with notes on the filters used (or potentially of use) in their observation and imaging. There are also notes on their celestial coordinates, magnitudes, and other pertinent information.